To sider af et spejlhav, adskilt fra hinanden af et fælles sprog? Kroppen i narrativ antropologi og videnskabelig medicin - Frankenberg, Ronald (Tidsskriftet Antropologi, 2019)
This paper addresses the vexed question of the intellectual relationships between physicians and medical anthropologists sometimes incorporated in the same body. It suggests that they are more divided than they think because neither side always recognises that the former are, by definition, required to be pragmatic and the latter, analytical. They are less divided than they think because both groups have recently moved towards focusing their study on the body; physicians rather than just on the diseased part, anthropologists instead of on reified, but disembodied, culture. The new developments, however, may lead to the concealing and reinforcing of a deeper division based on their diverse ways of seeing the body. They use each other as mirrors and, as through a glass darkly, see themselves as the despised other, and others as an esteemed self.